2023
DOI: 10.1021/jacs.2c13220
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective C(sp3)–C(sp3) Reductive Cross-Electrophile Coupling of Unactivated Alkyl Halides with α-Chloroboronates via Dual Nickel/Photoredox Catalysis

Abstract: Substantial advances in enantioconvergent C(sp3)–C(sp3) bond formations have been made with nickel-catalyzed cross-coupling of racemic alkyl electrophiles with organometallic reagents or nickel-hydride-catalyzed hydrocarbonation of alkenes. Herein, we report an unprecedented enantioselective C(sp3)–C(sp3) reductive cross-coupling by the direct utilization of two different alkyl halides with dual nickel/photoredox catalysis system. This highly selective coupling of racemic α-chloroboronates and unactivated alky… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
23
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(24 citation statements)
references
References 70 publications
0
23
0
1
Order By: Relevance
“…Very recently, a cross-coupling of α-trifluoromethyl alkyl bromides and aryl halides to deliver benzylic trifluoromethylation products under dual nickel/photoredox catalysis system has been developed in our group. , Considering that tetrabutylammonium decatungstate (TBADT) can serve as an efficient hydrogen-atom-transfer (HAT) photocatalyst for the acyl C–H activation of aldehydes, we envisioned a coupling of α-trifluoromethyl alkyl bromides and aldehydes could provide a facile and modular route to obtain α-CF 3 ketones (Scheme bottom). Importantly, by the utilization of various substrates, the CF 3 group can be selectively installed into any one side of the carbonyl which can well circumvent the aforementioned problems in the enolate process.…”
mentioning
confidence: 99%
“…Very recently, a cross-coupling of α-trifluoromethyl alkyl bromides and aryl halides to deliver benzylic trifluoromethylation products under dual nickel/photoredox catalysis system has been developed in our group. , Considering that tetrabutylammonium decatungstate (TBADT) can serve as an efficient hydrogen-atom-transfer (HAT) photocatalyst for the acyl C–H activation of aldehydes, we envisioned a coupling of α-trifluoromethyl alkyl bromides and aldehydes could provide a facile and modular route to obtain α-CF 3 ketones (Scheme bottom). Importantly, by the utilization of various substrates, the CF 3 group can be selectively installed into any one side of the carbonyl which can well circumvent the aforementioned problems in the enolate process.…”
mentioning
confidence: 99%
“…Indeed, numerous studies built off of those seminal findings to combine electrophilic ester and amide derivatives with olefins under Ni-catalysis (Figure A). In 2022, the Fu group further demonstrated that in situ generated Reformansky-type reagents could be coupled to alkyl halides in an enantioselective fashion (Figure B) . Recent findings from the Xu group have subsequently demonstrated that two electrophiles such as α-halo boronic esters and alkyl halides could also be coupled with high enantiocontrol under photoreductive conditions (Figure C) . Meanwhile, doubly decarboxylative cross coupling (dDCC) has emerged as a powerful method to construct Csp 3 –Csp 3 bonds under electrochemical conditions (with and without Ni, Figure D). In this Communication, the first examples of enantio- and diasteroselective dDCC between redox-active esters (RAEs) derived from readily available alkyl carboxylic acids and malonate derivatives are disclosed .…”
mentioning
confidence: 99%
“…8 Recent findings from the Xu group have subsequently demonstrated that two electrophiles such as α-halo boronic esters and alkyl halides could also be coupled with high enantiocontrol under photoreductive conditions (Figure 1C). 9 Meanwhile, doubly decarboxylative cross coupling (dDCC) has emerged as a powerful method to construct Csp 3 −Csp 3 bonds under electrochemical conditions (with and without Ni, Figure 1D). 10−12 In this Communication, the first examples of enantio-and diasteroselective dDCC between redox-active esters (RAEs) derived from readily available alkyl carboxylic acids and malonate derivatives are disclosed.…”
mentioning
confidence: 99%
“…Halomethylorganoboron reagents have been shown to display several different reactivity profiles, including metalation, boronate formation, and the formation of a-boryl radicals; however, examples of oxidative addition to this reagent class remain rare and are principally achieved using Ni catalysis. For example, Fu demonstrated stereoconvergent crosscoupling of racemic a-chloroboronic acid esters with organozinc reagents, 40,41 while Martin first showed crosselectrophile coupling [42][43][44] and alkene difunctionalization using a-bromoboronic acid esters. 45 Within Pd catalysis, Gevorgyan has developed Heck reactions based on a single-electron transfer (SET) manifold.…”
mentioning
confidence: 99%
“…Several heterocycles were well tolerated including thiophenes (39)(40)(41), pyridine (42), furans (43,44), and isoxazole (45). Some limitations of the boronic acid scope included specific functional groups (46,47), heterocycles (48, 49), styrene boronic acid (50), and alkylboronic acids (51).…”
mentioning
confidence: 99%